An atypical new species of Bothryonopa (Coleoptera, Chrysomelidae, Cassidinae, Bothryonopini) from south India - Shameem, K. M. (Zootaxa, 2019)
Bothryonopa sahyadrica n. sp., an atypical new species of the genus from southern Western Ghats biodiversity hot-spot in India is described and illustrated. The new species lacks ventral spine on all femora, in contrast to majority of the members of the genus, including the type species. Pronotum is anteriorly distinctly narrower than posteriorly with evenly curved anterolateral corners in the new species, while pronotum in the typical species is widest medially and not distinctly narrowed anteriorly. Host plant of B. sahyadrica n. sp. is Calamus gamblei Becc. & Hook. f. (Arecaceae).